2016
DOI: 10.1039/c6cc02856j
|View full text |Cite
|
Sign up to set email alerts
|

An effective host material with thermally activated delayed fluorescence formed by confined conjugation for red phosphorescent organic light-emitting diodes

Abstract: A thermally activated delayed fluorescence material 2,6-bis(9,9-diphenylacridin-10(9H)-yl)pyrazine was designed and synthesized. The twisted configuration made it possesses very small singlet-triplet splitting. A red electroluminescent device based on this new host material is able to achieve ∼26% external quantum efficiency and relatively flat efficiency roll-off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…As observed in Figure 8, both hole and electronc urrents of the cohost-based single-carrier devices are improved;t he hole current improved more significantly,p robablyd ue to the existence of an electron-rich component in the cohost. Thus, the improved carrier transporting property,w hich is beneficial for enlargement of the carrier recombination zone, is believed to be ar eason for the much improved performance of the two OLEDs.T he triplet-exciton upconversion of the exciplex, which was demonstrated to be able to reducet he triplet-triplet and triplet-polaron annihilation in the emitting layer, [16] shoulda lso be an important reasonf or the performance improvement of these devices. So far,t he lifetime of the devices have not been investigated due to the limitation of related instrumentsi no ur laboratory.I tw as demonstrated that the unencapsulated OLEDs in this study were electrically stable during the measurementso fE Ld ata in air.O nthe other hand, the device lifetime is not only dependento nt he emitting layer,b ut also strongly governed by the hole and electron-transporting layers and other organic functional layers.…”
Section: Resultsmentioning
confidence: 99%
“…As observed in Figure 8, both hole and electronc urrents of the cohost-based single-carrier devices are improved;t he hole current improved more significantly,p robablyd ue to the existence of an electron-rich component in the cohost. Thus, the improved carrier transporting property,w hich is beneficial for enlargement of the carrier recombination zone, is believed to be ar eason for the much improved performance of the two OLEDs.T he triplet-exciton upconversion of the exciplex, which was demonstrated to be able to reducet he triplet-triplet and triplet-polaron annihilation in the emitting layer, [16] shoulda lso be an important reasonf or the performance improvement of these devices. So far,t he lifetime of the devices have not been investigated due to the limitation of related instrumentsi no ur laboratory.I tw as demonstrated that the unencapsulated OLEDs in this study were electrically stable during the measurementso fE Ld ata in air.O nthe other hand, the device lifetime is not only dependento nt he emitting layer,b ut also strongly governed by the hole and electron-transporting layers and other organic functional layers.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al developed the TADF compound PrDPhAc (Δ E ST : 0.07 eV) and applied it as a host for red phosphors such as [ Ir(MDQ) 2 (acac)] ( Figure ). The OLED achieved an EQE of 25.8% with CIE coordinates of (0.61, 0.39), much higher than the 12.4% EQE reported when using CBP as host.…”
Section: Tadf Emitters Employed As Host Materialsmentioning
confidence: 99%
“…Recently, many bipolar hosts have been developed to improve the device efficiency and lifetime of red phOLEDs. Developed bipolar host is composed of a number of electron acceptors (quinazoline, quinoxaline, triazine, oxadiazole, and imidazole) [2][3][4][5] and electron donor (carbazole, diazacarbazole, diphenylacridine and phenothiazine) [6][7][8][9] and proved that a number of bipolar hosts can show higher than 20% EQE in red phOLEDs but still many bipolar hosts with high efficiency and long lifetime have not yet been reported. [10][11][12] Herein, two bipolar hosts, 7-(4-(4,6-diphenyl-1,3,5-triazin-2yl)phenyl)-7H-benzo[c]carbazole (BCTrz1) and 7-(3-(4,6diphenyl-1,3,5-triazin-2-yl)phenyl)-7H-benzo[c]carbazole (BCTrz2), are introduced as red hosts for Ir(mphmq) 2 (tmd) [Iridium(III)bis(4-methyl-2-(3,5-dimethylphenyl)quinolinato-N ,C2′) tetramethylheptadionate] phosphorescent emitter.…”
Section: Objective and Backgroundmentioning
confidence: 99%